Exosomes derived from first-trimester human decidual mesenchymal stem cell - Yuxian Wang; Linping Jin; Miaojie Fang; Xujia Huang; Jian Xu (Tissue and Cell, 2026)

Study on alkyl sulfonate enhanced sulfidization-amine flotation of fine-grained smithsonite based on foam stability regulation - Shuangrong Deng; Ximei Luo; Linping Qi; Xingchen Leng; Jianing Lv; Yuqiao Feng; Yunfan Wang (Minerals Engineering, 2026)

Continuous hollow spiral microfibers with embedded microchannels for synergistically enhanced atmospheric water harvesting and storage - Yuqiu Guo; Yalan Liu; Chuanjiyue Zhou; Ze Lv; Qianqian Wang; Wei Wu; Bolin Ji; Linping Zhang; Xueling Feng; Hong Xu; Zhiping Mao (Chemical Engineering Journal, 2026)

Microenvironment-regulated Fe single-atom nanozyme with neutral-pH peroxidase-mimicking activity for paper-based multiplexed biomarker detection - Rong Huang; Linping Tian; Dongmei Deng; Xiaoxia Yan; Haibo He; Wei Wang; Liqiang Luo (Analytica Chimica Acta, 2026)

Inflammatory mediators link occupational aluminum exposure to domain-specific cognitive impairment: Evidence from a cross-sectional study - Shihui Guo; Hongjie Jiang; Yujun Ma; Jiaping Huan; Baolong Pan; Jing Song; Linping Wang; Huifang Zhang; Xiaoting Lu (NeuroToxicology, 2026)

Effects of size-specific particulate matter on acute lower respiratory infection in children under 3 years of age: A ten-year time-series study in Foshan, China - Linping Chen; Jiayi Liang; Zihan Lin; Zitong Zhuang; Lan Chen; Xiaojie Wang; Xiangming Zhong (Atmospheric Environment, 2026)

The association between mixed exposure to multiple metals and the risk of abnormally elevated blood glucose among aluminum factory workers - Yifeng Zhang; Yulu Xin; Mujia Li; Hao Xu; Xin Guo; Linping Wang; Huifang Zhang; Jinzhu Yin; Xiaoting Lu; Baolong Pan; Jing Song (Environmental Geochemistry and Health, 2026)

Effect of plant litter burial on soil dissolved organic matter in the Yellow River Delta wetland, China - Linping Xie; Yutong Yan; Min Wang; Guangang Hu; Xia Sun; Jianbu Wang; Ming Xin; Qinsheng Wei; Baodong Wang (Marine Environmental Research, 2026)

Utilization of sintering red mud as a solid waste-based foaming agent for warm mix asphalt: modification mechanism and performance evaluation - Xuehao Luan; JunYao Hui; Jing Gao; Ming Liang; Xingchi Zhao; Xin Wang; Linping Su (Journal of Cleaner Production, 2026)

Kalirin as a key mediator of aluminum-induced cognitive dysfunction and neurotoxicity: Integrated evidence from occupational and cellular studies - Le Zhao; Jinzhu Yin; Mingxing Li; Yujun Ma; Shihui Guo; Guangsen Feng; Jing Song; Linping Wang; Huifang Zhang; Baolong Pan; Xiaoting Lu (Chemico-Biological Interactions, 2026)

A moderated mediation of tau phosphorylated sites in the association between occupational aluminum exposure and cognitive function - Yujun Ma; Guangsen Feng; Shihui Guo; Jing Song; Linping Wang; Huifang Zhang; Jinzhu Yin; Xiaoting Lu (NeuroToxicology, 2025)

Synergistic confinement and heavy atom effects in carbon dots for enhanced phosphorescence: Matrix-free and matrix conditions - Rui Li; Linping Zhang; Ji Fan; Bijia Wang; Hong Xu; Zhiping Mao (Chemical Engineering Journal, 2025)

Aluminum Exposure Leads to Aβ Deposition via the ciRs-7 Pathway - Lei Zhang; Yonghao Ma; Hailun Fang; Yujuan Gong; Chenyang Li; Huaxing Meng; Jing Song; Xiaoting Lu; Huifang Zhang; Qiao Niu; Linping Wang (Biological Trace Element Research, 2025)

Janus-structured thermally conductive radiative cooler for electronic devices heat dissipation - Xiuyan Yan; Jinru Liu; Linping Zhang; Yi Zhong; Bolin Ji; Wei Wu; Bijia Wang; Xueling Feng; Liduo Rong; Hong Xu; Zhiping Mao (Chemical Engineering Journal, 2025)

PDZD8 Dysregulation Mediates RVLM Neuronal Hyperexcitation Via Activation of Ca2+-Calpain-2 Signaling in Stress-Induced Hypertension - Tianfeng Liu; Linping Wang; Lei Tong; Zhangyan Ren; Bingjie Zhao; Haisheng Liu; Wen Lu; Haili Zhang; Shuai Zhang; Dongshu Du (Molecular Neurobiology, 2025)

A refined two-stage microalgal phosphorus uptake model incorporating enzymatic delay dynamics improves predictive accuracy - Jinfeng Han; Wei Cao; Linping Tang; Chunji Jin; Yangguo Zhao; Yi Wang; Liang Guo (Chemical Engineering Journal, 2025)

Differential AMF diversity in the rhizosphere and endosphere of two Camellia oleifera cultivars - Yuxuan Huang; Zhen Wang; Shaohua Huang; Jia Cao; Fei Wu; Linping Zhang (Applied Soil Ecology, 2025)

Occupational aluminum exposure in northern China’s large-scale plants: Unveiling dual-pathway mediation of fasting blood glucose and systolic blood pressure in cognitive impairment among workers - Xin Guo; Qiang Yang; Fangyu Gao; Baolong Pan; Feng Gao; Jingsi Zhang; Shanshan Wang; Xiaoting Lu; Jing Song; Linping Wang; Huifang Zhang; Qiao Niu (NeuroToxicology, 2025)

Integrated physiological and proteomic analyses reveal differential responses of microalgae to inorganic phosphate forms in wastewater - Jinfeng Han; Wei Cao; Linping Tang; Chunji Jin; Yangguo Zhao; Yi Wang; Liang Guo (Journal of Environmental Chemical Engineering, 2025)

Optimization of Phaeodactylum tricornutum cultivation for enhancing mariculture wastewater treatment and high value product recovery using Box–Behnken design - Feng You; Yiwei Fan; Linping Tang; Xiangrong Liu; Chunji Jin; Yangguo Zhao; Yi Wang; Liang Guo (Process Safety and Environmental Protection, 2025)

The effects of occupational aluminum exposure on blood pressure and blood glucose in workers – A longitudinal study in northern China - Lingshan Xue; Shihui Guo; Jiaping Huan; Chenyang Li; Jing Song; Linping Wang; Huifang Zhang; Baolong Pan; Qiao Niu; Xiaoting Lu; Jinzhu Yin (Toxicology Letters, 2025)

The interaction between plasma polymetals and lifestyle on cognitive dysfunction in occupational aluminum exposed workers: A cross-sectional study in China - Tianshu Wang; Lingshan Xue; Chenyang Li; Dan Zhao; Jiaping Huan; Xiao Han; Jing Song; Linping Wang; Huifang Zhang; Qiao Niu; Baolong Pan; Jinzhu Yin; et al. (NeuroToxicology, 2024)

Perioperative complications of middle cerebral artery occlusion in rats alleviated by human umbilical cord mesenchymal stem cells - Liang Liu; Yating Luo; Tao Xu; Qisheng Tang; Jialian Yi; Linping Wang; Shixiang Luo; Zhaohong Bi; Jianlei Liu; Jun Lu; Weiwei Bi; Changguo Peng; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Super-hydrophilic carbonized wood-based solar steam evaporator: A novel approach to enhance freshwater generation - Hongfei Hu; Yingxuan Feng; Xinjie Chen; Linping Tian; Zhiyuan Yin; Huinan Wang; Yingying Li; Yushan Yang; Qingfeng Sun (Journal of Environmental Chemical Engineering, 2024)

LncRNA 51A: A promising diagnostic biomarker for assessing cognitive decline in occupationally exposed aluminum workers - Hailun Fang; Juan Li; Lei Zhang; Baichun Li; Jing Song; Xiaoting Lu; Qiao Niu; Linping Wang (Environmental Toxicology and Pharmacology, 2024)

Versatile Lamellar Wrap-Structured PVDF/PZT/CNTs Piezoelectric Sensor for Road Traffic Information Sensing, Monitoring, and Energy Harvesting - Ming Liang; Jianjiang Wang; Linping Su; Xue Xin; Zhenchao Chen; Yunfeng Zhang; Yuepeng Jiao; Xuehao Luan; Lin Chen; Zhanyong Yao (Chemical Engineering Journal, 2024)

A wood-inspired epoxy-based electronic packaging material with vertically aligned thermally conductive channels for electromagnetic waves absorption and thermal management - Jiawei Luo; Ze Lv; Qianqian Wang; Linping Zhang; Yi Zhong; Hong Xu; Zhiping Mao (Chemical Engineering Journal, 2024)

Analysis of aged microplastics: a review - Yanqi Shi; Linping Shi; Hexinyue Huang; Kefu Ye; Luming Yang; Zeena Wang; Yifan Sun; Dunzhu Li; Yunhong Shi; Liwen Xiao; Shixiang Gao (Environmental Chemistry Letters, 2024)
Microplastics are emerging contaminants that undergo progressive aging under environmental conditions such as sunlight irradiation, mechanical forces, temperature variations, and the presence of biological organisms. Since aging modifies microplastic properties, such as their own toxicity and the toxicity of trapped pollutants, advanced methods to analyze microplastics are required. Here we review methods to analyze microplastic aging with focus on the aging process, qualitative identification, quantitative characterization, and chemometrics. Qualitative identification is done by mechanical techniques, thermal techniques, e.g., thermal degradation and gas chromatography–mass spectrometry, and spectral techniques, e.g., infrared, Raman, fluorescent, and laser techniques. Quantitative characterization is done by microscopy and mass spectrometry. Microplastic aging results in a series of surface physical changes, biofilm formation, chemical oxidation, thermal alternation, and mechanical deterioration. Changes in mechanical and thermal properties allow to differentiate aged microplastics. Infrared and Raman spectroscopy are rapid and sensitive for chemical identification of microplastics in complex environmental samples. Combining two techniques is preferable for accurate detection and categorization.

Parabens promotes invasive properties of multiple human cells: A potential cancer-associated adverse outcome pathway - Linping Wang; Luyi Chen; Daniel Schlenk; Feixue Li; Jing Liu (Science of The Total Environment, 2024)

Flexible and wearable functional materials for ionizing radiation Protection: A perspective review - Hao Li; Linping Yan; Jibo Zhou; Yaping Wang; Xuepin Liao; Bi Shi (Chemical Engineering Journal, 2024)

Enhanced NMDA receptor pathway and glutamate transmission in the hippocampal dentate gyrus mediate the spatial learning and memory impairment of obese rats - Dingding Lv; Bin Xiao; Huaying Liu; Linping Wang; Yingshun Li; Yin Hua Zhang; Qinghua Jin (Pflügers Archiv - European Journal of Physiology, 2024)
Obesity has been linked with the impairment of spatial memory and synaptic plasticity but the molecular mechanisms remained unidentified. Since glutamatergic transmission and NMDA receptor neural pathways in hippocampal dentate gyrus (DG) are essential in the learning and memory, we aimed to investigate glutamate (Glu) and NMDA receptor signaling of DG in spatial learning and memory in diet-induced obesity (DIO) rats. Spatial learning and memory were assessed via Morris water maze (MWM) test on control (Ctr) and DIO rats. Extracellular concentration of Glu in the DG was determined using in vivo microdialysis and HPLC. The protein expressions of NMDA receptor subunit 2B (NR2B), brain-derived neurotrophic factor (BDNF), the activation of calcium/calmodulin-dependent kinase II (CaMKII) and cAMP-response-element-binding protein (CREB) in the DG were observed by western blot. Spatial learning and memory were impaired in DIO rats compared to those of Ctr. NR2B expression was increased, while BDNF expression and CaMKII and CREB activation were decreased in DG of DIO rats. Extracellular concentration of Glu was increased in Ctr on the 3rd and 4th days of the MWM test, but significant further increment was observed in DIO rats. Microinjection of an NMDA antagonist (MK-801) into the DG reversed spatial learning and memory impairment. Such effects were accompanied by greater BDNF expression and CaMKII/CREB activation in the DG of DIO rats. In conclusion, the enhancement of Glu-NMDA receptor transmission in the hippocampal DG contributes to the impairment of spatial learning and memory in DIO rats, maybe via the modulation of CaMKII-CREB-BDNF signaling pathway.

Disruption of gonadotropin hormone biosynthesis by parabens: A potential development and reproduction-associated adverse outcome pathway - Linping Wang; Xiaochen Liu; Manqi Zhao; Feixue Li; Jing Liu (Environmental Pollution, 2024)

Effects of pharmaceutical and personal care products on pubertal development: Evidence from human and animal studies - Linping Wang; Xiaoqing Ye; Jing Liu (Environmental Pollution, 2024)

Electric field–tunable self-sensing nanocomposites with aligned CNTs for in-situ pavement health monitoring: Electrodynamic alignment, sensor development, and performance validation - Linping Su; Xue Xin; Ming Liang; Jianjiang Wang; Xuehao Luan; Hao Wang; Yuepeng Jiao; Yunfeng Zhang; Zhanyong Yao (Chemical Engineering Journal, 2024)

A simulation-optimization approach based on the compound eutrophication index to identify multi-nutrient allocated load - Yanqun Yang; Keqiang Li; Shengkang Liang; Guohong Lin; Cheng Liu; Jixin Li; Linping Xie; Yanbin Li; Xiulin Wang (Science of The Total Environment, 2024)

Environment relevant exposure of perfluorooctanoic acid accelerates the growth of hepatocellular carcinoma cells through mammalian target of rapamycin (mTOR) signal pathway - Jiawei Hong; Xiaoyan Wang; Hangbiao Jin; Yuanchen Chen; Yifan Jiang; Keyi Du; Diyu Chen; Shusen Zheng; Linping Cao (Environmental Pollution, 2024)

Nuclear factor kappa B (NF-κB) participates in the aluminum-induced down-regulation of miR29a/b1 - Linping Wang; Jingqi Zhang; Yue Zhao; Juan Li; Xiaoting Lu; Jing Song; Ling Zhang; Qiao Niu (Journal of Trace Elements in Medicine and Biology, 2023)

Plume effects on Martian surface: Revealing evolution characteristics of plume-surface interaction at Tianwen-1 landing site - Pengwei Luo; Xiaoping Zhang; Renrui Liu; Mingjie Zhang; Cunhui Li; Yi Xu; Roberto Bugiolacchi; Baocheng Hua; Haiyan Zhang; Liansheng Li; Jilin You; Yanyan Xu; et al. (Engineering Geology, 2023)

Molecular mechanism of the carboxyl terminus of Hsc70-interacting protein in TAU hyperphosphorylation induced by AlCl3 in N2a cells - Baolong Pan; Fanpeng Kong; Xiaofen Ju; Jing Song; Linping Wang; Qiao Niu; Xiaoting Lu (Toxicology, 2023)

The diabetogenic effects of pesticides: Evidence based on epidemiological and toxicological studies - Yile Wei; Linping Wang; Jing Liu (Environmental Pollution, 2023)

Spatial Distribution and Seasonal Variation of Hypoxic Zone in the Eastern Equatorial Indian Ocean - Linping Xie; Baodong Wang; Ming Xin; Ying Wang; Xia Sun; Qinsheng Wei; Lin Liu; Chao Yuan (Journal of Ocean University of China, 2023)

Changes in miR-134-3p expression and zDHHC3-AMPARs axis in association with aluminum neurotoxicity - Jing Song; Wenjing Li; Chunman Yuan; Ting Gao; Xiaoting Lu; Linping Wang; Qiao Niu (Environmental Science and Pollution Research, 2023)

Robust orientation-3D conductive network enabled high-performance flexible sensor for traffic monitoring: Role of surface functionalization on self-assembled microspheres arrays - Linping Su; Ming Liang; Jianjiang Wang; Xue Xin; Yuepeng Jiao; Chuan Wang; Yunfeng Zhang; Zhanyong Yao (Chemical Engineering Journal, 2023)

Multi-hazard risk assessment of the Great Wall relics: a case study in the Miyun District, Beijing - Yingli Zhao; Sisi Wang; Ding He; Linping Jiang; Chunyi Li; Chundi Chen (Landscape and Ecological Engineering, 2023)

Barbican-inspired bimetallic core–shell nanoparticles for fabricating natural leather-based radiation protective materials with enhanced X-ray shielding capability - Hao Li; Jibo Zhou; Linping Yan; Rui Zhong; Yaping Wang; Xuepin Liao; Bi Shi (Chemical Engineering Journal, 2023)

Investigation of sludge disintegration using vortex cavitation circulating fluidised grinding technology - Liang Dong; Tong Zhao; Yahui Cui; Zhe Li; Linping Chen; Chaofan Pang; Yunqian Wang (Journal of Environmental Management, 2023)

Identification of a novel frameshift mutation in the SCNN1B causing Liddle syndrome - Yi Qu; Yiting Lu; Di Zhang; Xinchang Liu; Peng Fan; Jiexin Chen; Hanbo Zhang; Kunqi Yang; Tao Tian; Yi Zhou; Qiongyu Zhang; Yu Zhang; et al. (Science Bulletin, 2023)

Factors associated with dysglycemia and its post-surgical resolution in patients with pheochromocytomas - Lin Zhao; Xu Meng; Qiongyu Zhang; Yi Zhou; Ting Zhang; Tao Tian; Hua Fan; Huadong Zhu; Yecheng Liu; Fang Luo; Linping Wang; Weixian Yang; et al. (Science China Life Sciences, 2023)

Differences in the effectiveness of the high-efficient concentrated pretreatment method on the norovirus detection in oysters and mussels - Yijing Li; Liang Xue; Junshan Gao; Weicheng Cai; Yanhui Liang; Zilei Zhang; Linping Wang; Xiaojing Hong; Luobing Meng; Mingfang Xu; Qingping Wu; Jumei Zhang (International Journal of Food Microbiology, 2023)

Forecasting and analysis of the effect of lifestyle on cognitive dysfunction induced by occupational aluminum exposure based on Bayesian networks - Dan Zhao; Xiao Han; Jiaping Huan; Dan Gao; Tianshu Wang; Jing Song; Linping Wang; Huifang Zhang; Tiane Luo; Baolong Pan; Qiao Niu; Xiaoting Lu (Environmental Toxicology and Pharmacology, 2023)

Physical-biogeochemical interactions and potential effects on phytoplankton and Ulva prolifera in the coastal waters off Qingdao (Yellow Sea, China) - Qinsheng Wei; Baodong Wang; Qingzhen Yao; Zhigang Yu; Mingzhu Fu; Junchuan Sun; Bochao Xu; Linping Xie; Ming Xin (Acta Oceanologica Sinica, 2019)

Expression Profiles of SIRT1 and APP Genes in Human Neuroblastoma SK-N-SH Cells Treated with Two Epigenetic Agents - Yaping Hou; Fanghua Wang; Linping Cheng; Tao Luo; Jie Xu; Huaqiao Wang (Neuroscience Bulletin, 2016)

Effects of Tamarisk shrub on physicochemical properties of soil in coastal wetland of the Bohai Sea - Xiuping He; Baodong Wang; Linping Xie; Ming Xin; Wei Wang; Zicheng Wang; Wenquan Zhang; Qinsheng Wei (Acta Oceanologica Sinica, 2016)

Recognition on the forming-vanishing process and underlying mechanisms of the hypoxia off the Yangtze River estuary - QinSheng Wei; BaoDong Wang; JianFang Chen; ChangShui Xia; DaPeng Qu; LinPing Xie (Science China Earth Sciences, 2015)